Pragmatics Analysis On Blaming Utterances In Aristocratic Movies Manuscript And Its Subtitling - Tinarah, Wachyu (2012)
This research aims at describing the variations of language form, the equivalence implicature, and the politeness strategies of blaming utterances used in aristocratic movies manuscript and its subtitling. The type of this research is descriptive qualitative. The technique of collecting data is documentation method, and the steps are watching the original movies, noting, retyping, coding, and analyzing the data of blaming utterances and its subtitling. To achieve the goals the writer uses linguistics form theory to identify the variation of language form in blaming utterances and its subtitling, Grice's theory of implicature to clarify the equivalence and non equivalence implicature, and to describe the equivalence and non equivalence Politeness strategies, the writer applies Brown and Levinson theory of politeness. The result of the study shows that the language form of blaming utterances in aristocratic movies manuscript and its subtitling shows that the most dominant types of sentence is in the form of and positive interrogative sentences which is subtitled into positive interrogative sentence . Whereas the implicature use on blaming utterances in aristocratic movies manuscript and its subtitling is 100% conversational implicature in the form of equivalence implicature. The most dominant politeness strategy of blaming utterances in aristocratic movies manuscript and its subtitling is in the form of bald of record. From the analysis variation of language form, equivalence and non equivalence of implicature and equivalence and non equivalence of politeness strategy on blaming utterances in aristocratic movies manuscript and its subtitling the writer found that usually upper class blames another upper class by using exclamatory sentence, upper class blames middle class by using declarative sentence, upper class blames lower class by using imperative sentence, Middle class blames upper class by using interrogative sentence, Middle class blames middle class by using interrogative sentence and lower class blames upper class by using declarative sentence. All of those are in the form equivalent of conversational implicature.